IFI16 reduced expression is correlated with unfavorable outcome in chronic lymphocytic leukemia. Issue 6 (18th May 2017) - Piccaluga, Pier Paolo; Agostinelli, Claudio; Righi, Simona; Ciccone, Maria; Re, Maria Carla; Musumeci, Giuseppina; Diani, Erica; Signoretto, Caterina; Bon, Isabella; Piccin, Ottavio; Cuneo, Antonio; Tripodo, Claudio; et al.
Abstract : Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults. Its clinical course is typically indolent; however, based on a series of pathobiological, clinical, genetic, and phenotypic parameters, patient survival varies from less than 5 to more than 20 years. In this paper, we show for the first time that the expression of the interferon‐inducible DNA sensor IFI16, a member of the PYHIN protein family involved in proliferation inhibition and apoptosis regulation, is associated with the clinical outcome in CLL. We studied 99 CLLs cases by immunohistochemistry and 10 CLLs cases by gene expression profiling. We found quite variable degrees of IFI16 expression among CLLs cases. Noteworthy, we observed that a reduced IFI16 expression was associated with a very poor survival, but only in cases with ZAP70/CD38 expression. Furthermore, we found that IFI16 expression was associated with a specific gene expression signature. As IFI16 can be easily detected by immunohistochemistry or flow cytometry, it may become a part of phenotypic screening in CLL patients if its prognostic role is confirmed in independent series.